THE EFFECT OF EARNING PER SHARE (EPS), LEVERAGE, COMPANY SIZE, TAX PLANNING AND INTEREST RATES ON STOCK RETURNS IN BANKING IN INDONESIA - Linatul Uyun (FEB Universitas Sultan Ageng Tirtayasa, 2023)
The purpose of the study is to find out and predict how much the independent variable, namely Earning Per Shares (EPS), Debt to Equity Ratio, company size, Tax Planning and interest rates, can affect the dependent variable, namely stock returns in conventional banking in 2018-2020. examined in this study were all conventional banks registered with the Financial Services Authority (OJK) and the Indonesia Stock Exchange in 2018-2020. The sampling technique was selected using the purposive sampling method, obtained 117 observational data. The analysis technique used in this research is multiple linear regression. The coefficient of determination, F test and t test as measuring tools used. The results of the study show that earnings per share (EPS), debt to equity ratio (DER), company size has no effect on stock returns, while tax planning and interest rates have a positive effect to stock returns.